Social Europe and Experimental Governance: Towards a New Constitutional Compromise? - Zeitlin, Jonathan (My University, 2005)
This paper examines the normative and empirical debates surrounding the use of the Open Method of Coordination in European social policy. The Open Method of Coordination is an experimental approach to European Union governance based on benchmarking national progress toward European objectives and organized mutual learning. Its potential benefits include reconciling the pursuit of common European concerns with respect to legitimate national diversity and encouraging cross-national learning through comparison of different approaches to similar problems across the European Union's 25 member states.